Repeated Chlamydia trachomatis infections are associated with lower bacterial loads. (2019) - Gupta, K.; Bakshi, R. K.; Van Der Pol, B.; Daniel, G.; Brown, L.; Press, C. G.; Gorwitz, R.; Papp, J.; Lee, J. Y.; Geisler, W. M.
Abstract: Chlamydia trachomatis (CT) infections remain highly prevalent. CT reinfection occurs frequently within months after treatment, likely contributing to sustaining the high CT infection prevalence. Sparse studies have suggested CT reinfection is associated with a lower organism load, but it is unclear whether CT load at the time of treatment influences CT reinfection risk. In this study, women presenting for treatment of a positive CT screening test were enrolled, treated and returned for 3- and 6-month follow-up visits. CT organism loads were quantified at each visit. We evaluated for an association of CT bacterial load at initial infection with reinfection risk and investigated factors influencing the CT load at baseline and follow-up in those with CT reinfection. We found no association of initial CT load with reinfection risk. We found a significant decrease in the median log10 CT load from baseline to follow-up in those with reinfection (5.6 CT/ml vs. 4.5 CT/ml; P = 0.015). Upon stratification of reinfected subjects based upon presence or absence of a history of CT infections prior to their infection at the baseline visit, we found a significant decline in the CT load from baseline to follow-up (5.7 CT/ml vs. 4.3 CT/ml; P = 0.021) exclusively in patients with a history of CT infections prior to our study. Our findings suggest repeated CT infections may lead to possible development of partial immunity against CT.